2015
DOI: 10.1016/j.ecoenv.2015.02.017
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in toxicity of coking wastewater to aquatic organisms by vertical tubular biological reactor

Abstract: We conducted a battery of toxicity tests using photo bacterium, algae, crustacean and fish to evaluate acute toxicity profile of coking wastewater, and to evaluate the performance of a novel wastewater treatment process, vertical tubular biological reactor (VTBR), in the removal of toxicity and certain chemical pollutants. A laboratory scale VTBR system was set up to treat industrial coking wastewater, and investigated both chemicals removal efficiency and acute bio-toxicity to aquatic organisms. The results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Interestingly, it was observed that photodegradation as an advance treatment increases the toxicity of wastewater on maize development. We can deduce from the studies that coking wastewater is one the most toxic industrial wastewaters, showing toxicity in all forms such as bio-toxicity, ecotoxicity, acute toxicity and genotoxicity (Zhou et al 2015;Na et al 2017;Smol et al 2018). Therefore, integrated advanced treatment using the physicochemical-biochemical combined process is necessary for reducing the toxicity of coking wastewater (Liu et al 2017b).…”
Section: Complexity and Toxicity Of Coking Wastewatermentioning
confidence: 99%
“…Interestingly, it was observed that photodegradation as an advance treatment increases the toxicity of wastewater on maize development. We can deduce from the studies that coking wastewater is one the most toxic industrial wastewaters, showing toxicity in all forms such as bio-toxicity, ecotoxicity, acute toxicity and genotoxicity (Zhou et al 2015;Na et al 2017;Smol et al 2018). Therefore, integrated advanced treatment using the physicochemical-biochemical combined process is necessary for reducing the toxicity of coking wastewater (Liu et al 2017b).…”
Section: Complexity and Toxicity Of Coking Wastewatermentioning
confidence: 99%
“…There are many efficient biosensors for toxicity sensing using different aquatic organisms like crustaceans, daphnia, algae, and fish (individually or as a battery of organisms). Microalgae (Pseudokirchneriella subcapitata) was identified as the most sensitive to any waterborne chemicals compared to others as well as being easy to culture and handle under laboratory conditions [17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic fraction of the this wastewater is mainly represented by phenol, cresols, resorcinols and dimethylphenols (DMP) [ 2 ], substances which are considered toxic, carcinogenic, mutagenic and teratogenic [ 3 ]. The DMPs, have shown to be even more persistent and toxic than other phenolic compounds [ 4 ] and they are often released to the environment in higher concentration than the permissible limits established [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%